Does Visitor Knowledge of Forest-based Ecosystem Services Reflect Distinct Behavioral Profiles? A Visitor Segmentation Analysis in Gunung CiremaiNational Park, Indonesia - Candra Wigati Hayuningsih; Prasetyo Nugroho (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
This study examines whether visitor knowledge of ecosystem services corresponds to distinct conservation behavior profiles in Gunung Ciremai National Park, Indonesia. We surveyed 452 visitors face to face using five-point scales to measure knowledge of provisioning, regulating and supporting, and cultural services, attitude toward conservation behavior, and self-reported environmental behavior. Latent scores were clustered with k-means, cluster centers were compared with t-tests, and pairwise correlations were assessed for the full sample and by segment. Two visitor segments emerged: Conservation Advocates (n = 243) and Conservation Supporters (n = 209). Conservation Advocates exhibit higher levels across the constructs and a clearer translation of favorable attitudes into reported actions, with regulating and supporting knowledge appearing especially consequential for behavior. Conservation Supporters show generally lower levels but a more tightly integrated knowledge structure, and provisioning knowledge functions as a practical entry point that links to both attitudes and actions. In the pooled sample, the three knowledge domains covary strongly and align with downstream outcomes, consistent with a konowledge–attitude–behavior sequence. Together, the matrix and table indicate that knowledge provides a common cognitive base, yet the pathway to action differs by segment. This study highlights the strategic importance of visitor segmentation in enhancing sustainable ecosystem management and promoting inclusive, behavior-focused conservation initiatives in protected tropical regions